Expression of breastmilk: qualitative exploration on challenges and experience of working women in Malaysia - Alwi, Nor Kamariah Mohamad (2023)
Breastmilk expression is a practice of extracting breastmilk to be stored and used for feeding infants. Women around the world has been practicing it for different reasons and using different methods and tools. However, there was lack of reference on milk expression among Malaysian working women. This study explored Malaysian working women views and experiences of on the expression of breastmilk, specifically on the reasons of practicing, influencing factors in choosing breastmilk expression method and their experiences in the practice. The initial participants were recruited through breastfeeding support groups from three locations in Malaysia which were Pulau Pinang, Kuala Lumpur and Kelantan. The subsequent participants were recommended by the earlier participants using snowballing technique. Face-to-face interviews were conducted using a semi structured interview guide with consented mothers of an infant age between three to twelve months old and were practicing any method of milk expression. All interviews’ sessions were audio recorded and transcribed verbatim. A total of 19 participants aged between 28 to 41 among Malay and Chinese were interviewed. All participants were working in various sectors with status of employment ranging from part time, flexible hours, full time workers, self employed and on leave. Each participant was practicing milk expression while continuing breastfeeding an infant aged between four to eleven months. The methods of breastmilk expression used were hand expression, breast pump and suction cup. Thematic analysis of the findings was presented into three sections which are reasons for practicing milk expression, influencing factors of milk expression method and experiences of milk expression. Four themes emerged from reasons for practicing milk expression were separation between mother and infant, milk production and supply concerns, direct feeding barriers and infant related reasons. Two themes emerged from the influencing factors in choosing milk expression method were internal influences and external influences. Four main themes emerged from the experiences of milk expression were milk expression practices, motivation in milk expressing, challenges in milk expressing and coping mechanism while facing challenges in milk expression. From the findings of reasons that emerged in this study, it showed that high determination of working mothers in Malaysia to continue providing breastmilk despite various challenges they were facing. The influencing factors in choosing milk expression method could provide descriptive information for practitioners to guide breastfeeding mothers in choosing their method. Further study involving multiple stakeholders should be considered to develop a comprehensive guide in supporting women in milk expression practices